Indonesia's Regulation and Implementation of Subsidies in View of Agreement on Subsidies and Countervailing Measures 1995-WTO - Eny Sholekhah (Universitas PGRI Madiun, 2024)
Regulation and implementation of subsidies in Indonesia is in the form of financial assistance provided by the government either directly or indirectly to companies, industries, industrial groups or exporters. With the aim of increasing export activities and reducing import activities for the welfare of the people and not violating the provisions of the 1945 Constitution, as the definition of subsidies is explained in the PP. Number 34 of 2011 concerning Anti-Dumping Measures, Compensatory Measures and Trade Security Measures Article 1 paragraph 8. In the Indonesian Government's policy, subsidies are given as long as they are to achieve people's welfare, and do not violate the order in the 1945 Constitution. However, in terms of government policy to improving people's welfare and protecting the domestic economy, often causing problems in the scope of international trade. This article aims to examine and understand how subsidies are regulated and implemented in Indonesia in terms of the Agreement On Subsidies And Countervailing Measures 1995-WTO. This research is normative legal research which examines written law based on applicable laws and regulations. The results of this research are that based on the policy issued by the Indonesian government, subsidies are given in order to realize the domestic economy, so based on this policy, basically the Agreement On Subsidies And Countervailng Measures 1995-WTO limits subsidies, so that their use does not cause harm to other countries' industries.